Description of three new species of Chaetabraeus (s. str.) from rock hyrax dens in South Africa, with notes on the ecology of species of the genus (Insecta, Coleoptera, Histeridae, Abraeinae) - (:unkn) unknown (My University, 2018)
Chaetabraeus (s. str.) tuberculatus n. sp. and C. (s. str.) francoisi n. sp. are very distinctive species described as new from South Africa. They are the only Chaetabraeus species which have a tubercle in each anterior pronotal angle. With Chaetabraeus (s. str.) johnstoni n. sp., they are the first histerid beetles collected in hyrax (Procavia capensis) dens. A synthesis of ecological data about the Chaetabraeus (s. str.) species is presented.
Keywords: African Research